Temperature Effect of Water Content at Hoarding Process Biosolar For Quality Maintain - Oksil Venriza; Ibnu Lukman Pratama (Jurnal Ilmiah Teknik Kimia, 2023)
Diesel fuel is used for diesel-engined vehicles containing sulfur, where the quality of diesel oil is expressed by the cetane number, as it is known that the cetane number for diesel fuel is 48. Water content is a parameter that affects the quality of diesel and biodiesel fuel which often increases during the stockpiling process. If the water content value is too high, it can damage the engine and accelerate corrosion. Hoarding for diesel and biodiesel products in this test was carried out with 2 variations, namely temperature variations (outside temperature and inside temperature) and also time variations. The length of the stockpiling process used in this study was 6 hours, where the results obtained from the water content test were also different. From the water content research for biodiesel products, the results were 0.1595% vol, 0.1621% vol for inside temperature, 0.1839% vol, and 0.1845% vol for outside temperature, while for solar products the results were 0.0344% vol, 0.0339% vol at inside temperature and 0.0502% vol and 0.0495 vol % for the outside temperature. It can be concluded that the higher the temperature in the process of storing diesel and biodiesel, the greater the value of the water content